2016
DOI: 10.20884/1.jm.2016.11.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Synthetic Optimization of Host Material Based on MIL-100(Fe)

Abstract: Electro-synthesis of Metal-Organic Frameworks types of MIL-100(Fe) (MIL = Material Institute of Lavoisier) in ethanol: water (1: 1) with electrolyte TBATFB 0.1 M has been optimized by varying voltage (12, 13, 14 and 15 Volt) and temperature (room temperature, 40, 60 and 80 °C). The product showed light brown powder which upon activation becomes dark brown. Optimum condition achieved during use voltage of 15 Volts and at a temperature of 40 °C with 33% yield. The obtained material was characterized by XRD and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…The histogram of 197 particle size distribution showed that the particle size ranged from 0.29 to 1.68 µm for MIL-100(Fe) and from 0.31 to 1.72 µm for MIL-100(Fe)-EDTA (see ESI Figure S3). The particle size of the materials in this study was smaller than those reported in the literature, which ranged from 0.4 to 8.6 µm (Lestari et al, 2016).…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx) and Transmition Electron Microscopy (Tem)contrasting
confidence: 67%
See 1 more Smart Citation
“…The histogram of 197 particle size distribution showed that the particle size ranged from 0.29 to 1.68 µm for MIL-100(Fe) and from 0.31 to 1.72 µm for MIL-100(Fe)-EDTA (see ESI Figure S3). The particle size of the materials in this study was smaller than those reported in the literature, which ranged from 0.4 to 8.6 µm (Lestari et al, 2016).…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx) and Transmition Electron Microscopy (Tem)contrasting
confidence: 67%
“…MIL-100(Fe) had the BET surface area of 722.433 m²/g and pore volume of 0.025 cc/g. Its surface area is higher than that of MIL-100(Fe) synthesized by Lestari et al (2016), but the pore volume is lower (surface area of 569.191 m²/g with pore volume of 0.4540 cc/g). The addition of EDTA to MIL-100(Fe) decreased its BET surface area to 587.253 m²/g.…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx) and Transmitionmentioning
confidence: 84%
“…Additionally, the low B.E shift of the deconvoluted-C1s XPS peak corresponding to the C–O chemical state of carbon indicates the involvement of −COOH group of BTC in the H-bonding as shown in Figure a. In the FTIR spectra, a low frequency shift of bands corresponding to CO stretch and O–H bend in the range 1738–1513 cm –1 evidenced the involvement of surface −COOH and −OH groups adsorbent in the H-bonding interaction . Other than the H-bonding, coordination bonding through the lone-pair containing sulfur or nitrogen of MB with the Fe ion in the catalyst is also a possible interaction involved in the adsorption process, as evident by the generation of a new multiplet in the Fe2p-spectra of Fe 2 O 3 -BTC (1:0.4) after MB adsorption (Figure S17b and Table S3).…”
Section: Results and Discussionmentioning
confidence: 94%
“…In the FTIR spectra, a low frequency shift of bands corresponding to CO stretch and O−H bend in the range 1738−1513 cm −1 evidenced the involvement of surface −COOH and −OH groups adsorbent in the H-bonding interaction. 51 Other than the H-bonding, coordination bonding through the lone-pair containing sulfur or nitrogen of MB with the Fe ion in the catalyst is also a possible interaction involved in the adsorption process, as evident by the generation of a new multiplet in the Fe2p-spectra of Fe 2 O 3 -BTC (1:0.4) after MB adsorption (Figure S17b and Table S3). Additionally, a low frequency shift in the bending vibration frequency (837.1 to 827.7 cm −1 ) corresponds to C-C het indicating the involvement of aromatic rings of MB in the interaction.…”
Section: Q Bqmentioning
confidence: 99%
“…MIL-101(Fe) was synthesized electrochemically adapted from Kumar et al [44] and Lestari et al [45] with several modification. Two pieces of iron electrodes were scrubbed using sandpaper, washed with HNO 3 (1 M) until shinny, and rinsed with water to remove the impurities.…”
Section: Synthesis Of Mil-101(fe)mentioning
confidence: 99%